Clinical-epidemiological profile of COVID-19 patients during the first wave of the disease in the state of Pará, Brazil - Cayres Vallinoto , Mariana; Cecy Rocha Lima, Aline; Nogueira Abreu, Isabella; Souza Lima, Sandra; Cayres Vallinoto, Izaura; Rosario Vallinoto, Antonio Carlos (Revista de Patologia Tropical / Journal of Tropical Pathology, 2022)
December 2019 saw several cases of pneumonia of unknown origin reported in Wuhan, China; the cause of this unknown disease was later identified as the new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The purpose of the present study was to evaluate the epidemiological profile of coronavirus disease 2019 (COVID-19) in the North Region of Brazil to assess possible correlations between demographic, social and health factors as well as adherence to safety protocols and the epidemiological profile of COVID-19. Information was obtained via a socio epidemiological survey carried out using Google Forms shared on various social media platforms from May 13 to 20, 2020. 6,781 people, living in the State of Pará, participated in the study of which only 682 (10.1%) had been diagnosed with COVID-19. Of these, 43 (6.3%) required hospitalization. 155 (23.5%) tested positive by RT-PCR associated with computed tomography. The RT-PCR test, with no association with other methods, was performed in 77 (11.6%) cases and serology performed in 360 cases (54.6%). There was a higher prevalence of confirmed cases (457, 67.0%) in females than in males, and the predominant age group was 30 to 40 years of age (214 participants, 31.4%). Considering the relatively homogeneous demographic profile of the sample, continued research is vital, preferably multi-centric studies, to obtain relevant data regarding the epidemiological dynamics of COVID-19; this data will allow the development of pandemic-prevention strategies that consider the social, cultural and political aspects of specific locations. KEY WORDS: COVID-19; epidemiology; pandemic.